Optimal Order of Servers for Tandem Queues in Light Traffic - Greenberg, Betsy S.; Wolff, Ronald W. (Management Science, 1988)
We study single-server stations in tandem, in which customers arrive according to a Poisson Process and are to be served at each of two servers. The order of the stations is assumed not to affect the quality of the service customers obtain. Using a light traffic approximation, we select (for various joint distributions of service time) the order of the stations that minimizes expected customer delay.